CHALLENGE OF AN ARBITRATOR AND ITS CONSEQUENCES - Varapnickas, Tadas (Teisė, 2016)
This article analyses the grounds for arbitrator’s removal and its consequences. The article reveals the contents of the challenge grounds stipulated by law, compares the grounds foreseen in Lithuanian law with the law of foreign countries, and examines direct and indirect consequences of arbitrator’s disqualification for arbitrator himself as well as for the arbitration proceedings.